2018
DOI: 10.1016/j.cell.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

The Basolateral Amygdala Is Essential for Rapid Escape: A Human and Rodent Study

Abstract: SummaryRodent research delineates how the basolateral amygdala (BLA) and central amygdala (CeA) control defensive behaviors, but translation of these findings to humans is needed. Here, we compare humans with natural-selective bilateral BLA lesions to rats with a chemogenetically silenced BLA. We find, across species, an essential role for the BLA in the selection of active escape over passive freezing during exposure to imminent yet escapable threat (Timm). In response to Timm, BLA-damaged humans showed incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 54 publications
11
155
0
1
Order By: Relevance
“…Pharmacological studies in rats have shown that administration of oxytocin into the central amygdala before recall of conditioned fear (context re-exposure) enhances freezing behaviour, whereas administration of an oxytocin receptor antagonist suppresses freezing behaviour in rats, suggesting that the oxytocin receptor in the central amygdala facilitates the expression of conditioned freezing behaviour. 106 100 Consistent with the facilitative role of oxytocin in fear conditioning, administration of an oxytocin agonist into the amygdala has been reported to enhance fear acquisition in juvenile rats.…”
Section: Central Amygdalamentioning
confidence: 83%
See 2 more Smart Citations
“…Pharmacological studies in rats have shown that administration of oxytocin into the central amygdala before recall of conditioned fear (context re-exposure) enhances freezing behaviour, whereas administration of an oxytocin receptor antagonist suppresses freezing behaviour in rats, suggesting that the oxytocin receptor in the central amygdala facilitates the expression of conditioned freezing behaviour. 106 100 Consistent with the facilitative role of oxytocin in fear conditioning, administration of an oxytocin agonist into the amygdala has been reported to enhance fear acquisition in juvenile rats.…”
Section: Central Amygdalamentioning
confidence: 83%
“…On the other hand, oxytocin has been suggested to facilitate active coping behaviour in certain conditions and to switch from passive stress-coping behaviour to active stress-coping behaviour. 24 Recently, oxytocin has been shown to reduce passive coping behaviour such as freezing behaviour by acting on neurones in the lateral part of the central amygdala, which inhibits the activity of periaqueductal gray-projecting central amygdala neurones, and, as a result, induces active escape behaviour 106 or active defensive behaviour. 269 Consistent with this idea, oxytocin has been shown to suppress social loss-induced passive coping behaviour in male prairie voles 84 and to induce social defeat-induced risk assessment behaviour (head orientation) in female mice by acting on the bed nucleus of the stria terminalis.…”
Section: Role S Of Ox Y To Cin In the Control Of Adap Tive B Ehaviomentioning
confidence: 86%
See 1 more Smart Citation
“…The CMA, with its reciprocal connections with the basal ganglia, midbrain, and brain stem, appears to be involved in allocating attention and generating the appropriate autonomic responses to environmental stimuli. In contrast, the BLA, with its connections to the CMA and with extensive cortical regions, is primarily involved in evaluating the emotional content of sensory inputs and plays a major role in threat responses (Mosher et al 2010;Terburg et al 2018). Although some post mortem evidence suggests that MDD selectively affects the receptors and number of nuclei in the BLA (Karolewicz et al 2009;Rubinow et al 2016), it is not clear if MDD is associated with larger or smaller BLA volume.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are some reports of improved SigAA learning with slightly longer or more complex WSs (Archer et al, 1984;Coll-Andreu et al, 1993;Levis and Stampfl, 1972;Satorra-Marin et al, 2001;Solomon and Brush, 1954;Terburg et al, 2018), this has not been systematically studied. There are far more studies of US imminence using Pavlovian paradigms.…”
mentioning
confidence: 99%